DESENTRALISASI PELAYANAN PUBLIK DI BIDANG ADMINISTRASI KEPENDUDUKAN DAN CATATAN SIPIL DALAM UPAYA PENINGKATAN KUALITAS PELAYANAN TERHADAP MASYARAKAT DI KABUPATEN BOMBANA - M.H, Hujriman (Muadalah : Jurnal Hukum, 2023)
Decentralization of public services in an effort to improve the quality of services to the community is an effort to realize prosperity in accordance with the constitutional mandate. The aim of this research is to determine the implementation and quality of public services in an effort to improve the quality of services to the community and to determine the obstacles and solutions in their implementation. The research method uses a sociological approach, data sources are primary and secondary data, with data collection methods in the form of literature study, observation and interviews. Then the data was analyzed using qualitative descriptive analysis. The results of this research show that the implementation of public services in the field of Population administration and civil registration in Bombana Regency, which includes Population Documents, Administrative Sanctions for Population and Civil Registration Events, and the Population Administration Information System (SIAK), the implementation and quality are not optimal. The obstacles faced are internal factors consisting of inadequate facilities and infrastructure and human resources, as well as external factors consisting of a lack of public awareness of the implementation of population administration, the vast administrative area of ​​Bombana Regency and the limited budget for implementation (SIAK).